Iz zala Konstitutsionnogo suda . Iz zala Konstitutsionnogo suda . From the Constitutional Court . Из зала Конституционного суда - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. The case of the constitutionality of the actions of the Communist Party (continued). Featured in the program: Khangel'dyev, Boris Bailievich (Lawyer); Katanian, Konstantin Aramovich (Journalist) Contributors: Menzelintsev, Igor' Borisovich (Anchor) Series description: Series of programs devoted to "The Case of the Communist Party; a 1992 court case, where the Russian Constitutional Court considered the constitutionality of the decree of President Yeltsin to suspend the activities of the Communist Party of the Soviet Union and theCommunist Party of the Russian Soviet Federative Socialist Republic, their property and dissolution. The case was filed at the request of 37 deputies of Russia. Дело о конституционности действий коммунистической партии (продолжение). В программе участвуют: Хангельдыев, Борис Байлиевич (Юрист); Катанян, Константин Арамович (Журналист) Создатели: Мензелинцев, Игорь Борисович (Ведущий/Ведущая) Описание серии: Цикл передач, посвященных "Делу КПСС" - судебному делу 1992 года, в котором Конституционный суд Российской Федерации рассмотрел вопрос о конституционности указов президента Ельцина о приостановке деятельности КПСС и КП РСФСР, их имуществе и роспуске. Дело было заведено по ходатайству 37 народных депутатов России.